DEPOSITIONS OF JUDICIAL CONSIDERATION IN CRIMINAL PROCEEDINGS - Сеник, Тарас Богданович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: to reveal the legal nature of the trial postponement in criminal proceedings. Methods of research: it has been defined a list of normative acts in this area. It also has been analyzed different approaches to the definition of the concept of postponement of the trial. Results: it has been analyzed the problems with the definition of the most characteristic features of trial postponing in criminal proceedings, which significantly distinguish it from other related concepts. Discussion: the introduction of amendments to the legislation regarding the definition of the concept of «postponing trial in criminal proceedings».